ANALISIS DAERAH RAWAN KECELAKAAN LALU LINTAS - Bolla, Margareth Evelyn; Messah, Yunita A.; Bunga Koreh, Michal M. (Jurnal Teknik Sipil, 2013)
The Timor Raya street that connects Kupang City to the district of Kupang has a high risk level of traffic accidents. The aims of this study are to find out the accidents rate and to spot the black sites on Timor Raya road at KM 02 – KM 11 of Kupang City, Nusa Tenggara Timur Province. The data of the traffic accidents in 2009 to 2011 were taken from Bhayangkara Hospital of Kupang City. To calculate the accident rates, the Equivalent Accident Number (EAN) method was applied, and to determine the black sites, the BKA (Batas Kontrol Atas) method and the Upper Control Limit (UCL) method were used. The results of the analysis showed that the KM 07 (EAN = 288) and KM 08 (EAN = 249) were identified as black sites because their accident rates EAN were higher than the limit control of BKA and UCL, where on the KM 07 BKA=142, UCL=141 and KM 08 BKA=142, UCL=139.